Posttransplant Hemophagocytic Lymphohistiocytosis Driven by Myeloid Cytokines and Vicious Cycles of T-Cell and Macrophage Activation in Humanized Mice - Yoshihara, Satoshi; Li, Yuying; Xia, Jinxing; Danzl, Nichole; Sykes, Megan; Yang, Yong-Guang (Frontiers in Immunology, 2019)
Hemophagocytic lymphohistiocytosis (HLH) has recently been increasingly reported as an important complication after stem cell transplantation, in line with the increase in the number of HLA-mismatched transplantation. Although previous clinical studies have shown an elevation of inflammatory cytokines in patients with HLH after hematopoietic stem cell transplantation, as well as those after viral infection or autoimmune disease, the disease pathogenesis remains poorly understood. Here we explored this issue in humanized mice with functional human lymphohematopoietic systems, which were constructed by transplantation of human CD34+ cells only, or plus human fetal thymus into NOD/SCID/c-/- (NSG) or NSG mice carrying human SCF/GM-CSF/IL-3 transgenes (SGM3). In comparison with humanized NSG (huNSG) mice, huSGM3 mice had higher human myeloid reconstitution and aggressive expansion of human CD4 memory T cells, particularly in the absence of human thymus. Although all huNSG mice appeared healthy throughout the observation period of over 20 weeks, huSGM3 mice developed fatal disease characterized by severe human T cell and macrophage infiltrations to systemic organs. HuSGM3 mice also showed severe anemia and thrombocytopenia with hypoplastic bone marrow, but increased reticulocyte counts in blood. In addition, huSGM3 mice showed a significant elevation in inflammatory cytokines including IL-6, IL-18, IFN-, and TNF-, faithfully reproducing the HLH in clinical situations. Our study suggests that posttransplant HLH is triggered by alloresponses (or xenoresponses in our model), driven by myeloid cytokines, and exacerbated by vicious cycles of T-cell and macrophage activation.